Does the Asian financial crisis affect the causal relationships between the United States and Asian stock markets? - Seah, Fang Eng. (2008)
This paper employed the Pairwise Granger Causality technique to examine the effect of the Asian Financial Crisis on the causal relationships between the United States and Asian stock markets, namely Singapore, Hong Kong, Korea, Malaysia and Taiwan. Data of stock return indices between the time period 1998 – 2002 are used. The test results show that there seem to be a rising trend of closer interrelationships between the markets before the crisis. In the post-crisis period, the test results reveal that the crisis has no impact on weakening the interrelationships between the markets. One explanation postulated could be due to the progress in financial liberalization of the Asian markets. This study also suggests that capital controls may have effect on the causal relationships between the markets.